Health Promotion in Schools: A Small Scale Study of the Perceptions of Teachers and Learners at A Senior Secondary School in Botswana - Lewanika, Annah (2008)
This study aims to explore the perceptions of teachers and learners with regard to health promoting programs in secondary education in Botswana. Health promotion is defined as a holistic process which enables people to increase control over and improve their health. Two focus group discussions were conducted and a total of eight teachers and eight learners participated. A schedule of questions for the focus group discussion was developed from the review of related literature and the questions were used to probe teachers and learners views on the effectiveness of health promotion in secondary schools. The discussions were recorded with an audio tape and the data were transcribed and analyzed searching for common themes and divergent views. The findings indicate that teachers and learners perceive healthpromotion as an integral part of education. However they recognized the limitations of implementing a comprehensive health promoting programin the school. Students also highlighted the importance of being consulted when health programs are planned for them in schools. Teachers supported the importance of policy formulation to guide the implementation of a comprehensive health promoting program. The outcomes of the study therefore suggest that there is a need to create awareness for all concerned - teachers, learners, parents and the wider community, of the importance of health promoting programs in schools.Further research is also suggested to explore attitudes of teachers and learners in the successful implementation of health promoting programs.